Pengaruh Integrated Circuit Pada Rangkaian Fastcharging Baterai Mobil Listrik - Tulus Asmoro, Purwandito; Dieta Wahyu Asry Ningtias; Widodo; Aziz Yulianto Pratama; Ali nur Fatoni (LPPM Politeknik Enjinering Indorama, 2025)
Transportation is the most important need in the mobility of fulfilling people's needs. The increasing number of transportation has an impact on environmental degradation, especially air pollution. Based on the Ministry of Environment and Forestry (KLHK), transportation contributes more than 20% of the total Carbon Dioxide (CO2) emissions in Indonesia. This is caused by conventional transportation or vehicles that use oil fuel (BBM). In addition to polluting the air, the use of conventional vehicles also triggers respiratory diseases that will worsen the quality of human life. Electric cars are one solution to overcome this problem because electric cars do not emit carbon emissions. Electric cars continue to be developed through industrial technology research including fast charging circuit architecture topology, power flow, and protection. Fast charging or fast charging of electric car batteries is needed to increase comfort, efficiency, and speed up time. Electric cars that have been designed by the Electrical Technology of the Indorama Engineering Polytechnic require a compatible fast charging circuit. The study aims to analyze the effect of Integrated Circuit (IC) 7805 and IC 7812 on fast charging of electric battery cars. The results of the study showed that the best performance criteria were obtained in the fast charging circuit using the IC 7805. A more stable voltage profile compared to circuits without IC, with an average of 12V. The current flowing is also high, which is 4 amperes, compared to other circuits, so that the charging time is faster, which is 8.75 hours compared to the circuit without IC, which takes 9.64 hours to charge the battery. Therefore, the addition of IC 7805 is proven to be compatible in the fast charging circuit of electric car batteries.